Third-Party vs. Second-Party Control: Disentangling the Role of Autonomy and Reciprocity - Gabriel Burdín; Simon Halliday; Fabio Landini (Institute for the Study of Labor (IZA), 2015)
This paper studies the role of autonomy and reciprocity in explaining control averse responses in principal-agents interactions. While most of the social psychology literature emphasizes the role of autonomy, recent economic research has provided an alternative explanation based on reciprocity. We propose a simple model and an experiment to test the relative strength of these two motives. We compare two treatments: one in which control is exerted directly by the principal (second-party control); and the other in which it is exerted by a third party enjoying no residual claimancy rights (third-party control). If control aversion is driven mainly by autonomy, then it should persist in the third-party treatment. Our results, however, suggest that this is not the case. Moreover, when a third party instead of the principal exerts control, control results in a greater expected profit for the principal. The implications of these results for organizational design are discussed.
Keywords: C72; C91; D23; M54; 330; third party; second party; control aversion; autonomy; principal-agent game; social preferences; trust; reciprocity